Solutions of fractional kinetic equation and the generalized Galué type Struve function. Issue 7 (3rd October 2019) - Suthar, D. L.; Habenom, Haile; Nisar, Kottakkaran Sooppy
Abstract: This paper aims to establish extensive form of the fractional kinetic equation involving generalized Galué type Struve function using the technique of Sumudu transform. Further, numerical values of the results are interpreted and their graphical interpretation of the solutions by employing MATLAB is given. The results obtained here are quite general and capable of yielding a very large number of known and new results.